Quality of Life in the Elderly Qur'an Memorizers - Taufik, Taufik; Lestari, Rini; Ashfi Raihana, Permata (Universitas Muhammadiyah Surakarta, 2024)
The present study aimed to investigate the quality of life of elderly Qur'an memorizers. Nine elderly Muslims who live in several regions in Java Island, Indonesia, were involved as informants. The informant was recruited by purposive sampling. The data collection method used a semi-structured interview technique. Data analysis used phenomenological techniques to uncover research objectives. The result showed that: In general, the memorizing Qur'an has an important influence on the elderly's quality of life. Specifically, the quality of life of the elderly can be seen in the improvement of several areas such as patience, self-concept, self-esteem, ability to remember, and self-confidence. In addition, the elderly felt that their role was more accepted by the community, one of whom was trusted to teach the Qur'an in the mosque.